Overdose of oral contraceptive pills as a means of intentional self-poisoning amongst young women in Sri Lanka: considerations for family planning. Issue 2 (22nd March 2016) - Weerasinghe, Manjula; Konradsen, Flemming; Eddleston, Michael; Pearson, Melissa; Agampodi, Thilini; Storm, Frederikke; Agampodi, Suneth
Abstract : Objective: Oral contraceptive pills (OCPs) are one of the most popular family planning methods in Sri Lanka. As part of two hospital-based studies on self-harm, the use of OCPs was identified, from yet unpublished results, as a means of intentional self-poisoning. To inform future guidelines for better OCP promotion, this article aims to describe the extent, patient characteristics and outcomes of OCP self-poisoning in the North Central Province of Sri Lanka. Methods: A secondary analysis was carried out on two hospital-based self-harm case series, from January 2011 to June 2014. Results: Fifty-four patients (52 women and two men) with an overdose of OCP as a means of intentional self-poisoning were admitted to one of the surveyed hospitals. The median age of the patients was 19 (interquartile range, 5) years. None of the patients were severely sick from their overdose and two-thirds of the patients were discharged within a day of admission. Intentional self-poisoning with OCPs represented less than 5% of all types of intentional medicine self-poisonings recorded at the hospitals. Information available for a subset of female patients indicates that many cases (13/23, 56.5%) were in their first year of marriage. Conclusions: More research is required to understand why young women in rural Sri Lanka overdose with OCPs as a means of intentional self-poisoning. Although the toxicity of OCPs is low and the public health significance of OCP poisoning remains minor, reproductive health service providers should be attentive to OCP overdose, monitor the development of this problem, and ensure appropriate information to OCP users.